Erdheim–Chester Disease With Multiorgan Involvement, Following Polycythemia Vera: A Case Report. Issue 20 (May 2016) - Iurlo, Alessandra; Dagna, Lorenzo; Cattaneo, Daniele; Orofino, Nicola; Bianchi, Paola; Cavalli, Giulio; Doglioni, Claudio; Gianelli, Umberto; Cortelezzi, Agostino
Abstract : Abstract: Erdheim–Chester disease is a rare form of non-Langerhans cell histiocytosis characterized by the migration and infiltration of lipid-laden CD68 +, CD1a − and S100 − histiocytes to various target organs, which leads to the disruption of physiological tissue architecture and reactive fibrosis, and thus impairs organ function. We describe the first case of a patient with Erdheim–Chester disease with multiorgan involvement developed after 6 years from polycythemia vera diagnosis. During the follow-up, an abdominal ultrasound scan revealed the presence of dense, bilateral perinephric infiltration. A computed tomographic guided core biopsy was performed in order to identify the histological nature of this lesion, and a morphological analysis demonstrated the accumulation of foamy histiocytes surrounded by fibrosis. The BRAF V600E mutation was detected, and a diagnosis of Erdheim–Chester disease was made. The extreme rarity of Erdheim–Chester disease strongly suggests the existence of potentially common element(s) that may have contributed to the pathogenesis of both disorders. Obviously, further studies are needed to clarify the mutual roles and effects of JAK2 and BRAF mutations in this patient, as well as their possible therapeutic implications.